O-2 Population and developmental pharmacokinetic analysis to evaluate and optimise cefotaxime dosing regimen in neonates and young infants. Issue 10 (20th September 2017) - Leroux,; Roué,; Gouyon,; Biran,; Zheng,; Zhao,; Jacqz-Aigrain,
Abstract : Background: Cefotaxime is one of the most frequently prescribed antibiotics for the treatment of Gram-negative bacterial sepsis in neonates. However, the dosing regi-mens routinely used in clinical practice vary considerably. The objective of the present study was to conduct a population pharmacokinetic study of cefotaxime in neonates and young infants in order to evaluate and optimise the dosing regimen. Methods: An opportunistic sampling strategy com-bined with population pharmacokinetic analysis using NONMEM software was performed. Cefotaxime concentrations were measured by high-performance liquid chromatography tandem mass spectrometry. Developmental pharmacokinetics-pharmacodynamics, the microbiological pathogens, and safety aspects were taken into account to optimise the dose. Results: The pharmacokinetic data from 100 neonates (gestational age [GA] range, 23 to 42 weeks) were modeled with an allometric two compartment model with first-order elimination. The median values for clearance and volume of distribution at steady state were 0.12 litre/h/kg of body weight and 0.64 litre/kg, respectively. The covariate analysis showed that current weight, GA, and postnatal age [PNA] had significant impacts on ce-fotaxime pharmacokinetics. Monte Carlo simulations demonstrated that the current dose recommendations underdosed the older newborns. A model-based dosing regimen of 50 mg/kg twice a day to four times a day, according to GA and PNA, was established. The associated risk of overdose for the proposed dosing regimen was 0.01%. Conclusion: We determined the population pharma cokinetics of cefotaxime and established a model based dosing regimen to optimise treatment for neonates and young infants.